An Analysis of the Big Five Personality (OCEAN) on The Characters in Garth Jenning's Movie Sing - Syamsul Bahri; Nurhikmah Siagian; Rehulina Tarigan (FKIP, Universitas Palangka Raya, 2024)
The big five personalities, such as conscientiousness, agreeableness, neuroticism, openness to experience, and extraversion, displayed by each character in the movie Sing. It provides insight into how to achieve goals and dreams despite numerous challenges in life, which makes it interesting to investigate. This objective of this research is to investigate the Big Five Personality of the characters in the movie Sing. This study takes a mixed-methods approach, combining descriptive qualitative analysis and content analysis, where scenes and speech from the movie were analyzed to discover and categorize the characters' personality qualities. The research findings on the Big Five personality traits in the movie Sing stated that extraversion reaches at 12.5%, while neuroticism, agreeableness and openness to experience each getting at 18.75%, and conscientiousness at 31.25%. The analysis of the Big Five Personality types in the movie finds a variety of characters embodying distinct features. Buster Moon exemplifies Extraversion, reaching at 12.5% of the attributes and showing a moderate level of friendliness and outgoing personality. Meena and Buster Moon both exhibit Neuroticism, reaching at 18.75% of their characters and emphasizing emotional depth and sensitivity. Rosita and Buster Moon embody Agreeableness to the same percentage as Neuroticism and openness to experience, stressing compassion and empathy throughout their interactions. Johny, Meena, and Buster Moon stand out in Conscientiousness, getting at 31.25% and demonstrating organizational and dependability. Johny and Buster Moon also have an Openness to Experience of 18.75%, indicating a willingness to explore new ideas and engage in creative efforts. Overall, this extensive analysis provides valuable insight into the diverse personalities shown in the movie Sing, expanding our understanding of how the Big Five Personality impact the characters' behaviors and interactions in the movie